Effect of water on the oxidation of CO by a Criegee intermediate. Issue 37 (16th September 2020) - Kumar, Amit; Mallick, Subhasish; Kumar, Pradeep
Abstract : The present work employs the CCSD(T)/CBS//M06-2X/aug-cc-pVTZ level of theory to investigate the effect of a water monomer and dimer on the oxidation of carbon-monoxide by a Criegee intermediate (CH2 OO). Abstract : The present work employs the CCSD(T)/CBS//M06-2X/aug-cc-pVTZ level of theory to investigate the effect of a water monomer and dimer on the oxidation of carbon-monoxide by a Criegee intermediate (CH2 OO). The present work suggests that in the presence of a water monomer the energy barrier of the title reaction reduced to ∼3.4 kcal mol −1 from the corresponding uncatalyzed barrier (∼12.4 kcal mol −1 ), whereas, in the presence of a water dimer it became as low as ∼−3.2 kcal mol −1 . It has also been found that, in the presence of catalysts, additional channels become available from which the title reaction can proceed. The estimated values of rate constants suggest that within the temperature range of 210–320 K, the effective bimolecular rate constant for the water monomer catalyzed channel is 10 to 100 times lower than the bimolecular rate constant of the uncatalyzed channel, whereas in the case of the water dimer it is ∼5–10 times higher than that of the uncatalyzed channel.